Palm Sugar Industry Development Strategy in Pernasidi Pondok Pring Village Banyumas - Ramadhani, Wanda Putri; Wiratno, Adi; Budiarti, Laeli (Faculty of Economics and Business, Jenderal Soedirman University, 2024)
Banyumas is very well known for its diverse culinary sector, such as palm sugar. To develop palm sugar products, an effective development strategy is needed based on SWOT analysis and business model canvas. The research method used is descriptive qualitative with data collection through interviews, observations, documentation. The sample studied was 10 sugar industries in Pernasidi Village, Pondok Pring, which have livelihoods that depend on the palm sugar industry. The development strategy carried out by researchers based on SWOT analysis is the SO strategy by utilizing the surrounding community as a workforce. WO strategy, cooperation is needed to increase productivity. ST strategy, maintaining the characteristics and quality of the product. WT strategy, holding HR training. Using the right strategy, it can reduce the problem in the development of the industry such as weather factors, lack of managerial skills, promotion, limited use of technology, and increasingly tight competition. The suggestions put forward are the need for the role of government in terms of marketing, education, subsidies, and regulation